2002
DOI: 10.1093/rheumatology/41.12.1413
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of nerve growth factor (NGF) and high affinity NGF receptor (p140 TrkA) in human osteoarthritic chondrocytes

Abstract: This is the first study showing that human chondrocytes synthesize NFG-beta and express on their surface the high affinity NGFR (p140 TrkA). Of note, NGF-beta and TrkA were upregulated in osteoarthritic chondrocytes suggesting a role of NGF in the pathophysiology of OA. We can speculate that NGF, like other growth factors, stimulates chondrocyte metabolism in the osteoarthritic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
95
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 30 publications
7
95
0
3
Order By: Relevance
“…We assessed the microarray data for genes that in previous studies were shown to be differentially expressed in intact versus damaged regions of OA cartilage from the same joint or in normal versus OA cartilage from different patients (4)(5)(6)(7)14,(34)(35)(36)(37)(38). The name and symbol of the reported genes are shown in Table 3.…”
Section: Results Of Real-time Quantitative Pcr Of Selected 8 Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed the microarray data for genes that in previous studies were shown to be differentially expressed in intact versus damaged regions of OA cartilage from the same joint or in normal versus OA cartilage from different patients (4)(5)(6)(7)14,(34)(35)(36)(37)(38). The name and symbol of the reported genes are shown in Table 3.…”
Section: Results Of Real-time Quantitative Pcr Of Selected 8 Genesmentioning
confidence: 99%
“…Therefore, changes in the gene expression patterns of chondrocytes in response to various exogenous stimuli could affect the integrity of articular cartilage. Based on this concept, many groups of investigators have reported that gene expression in certain molecules differ from region to region within a single OA joint (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…NGF receptors were also detected on activated murine CD4 T cells (but not on resting T cells) (43), human B lymphocytes (44), monocytes (45), skin and lung fibroblasts (46), keratinocytes (40), melanocytes (47), periarterial connective tissue cells (40), and human osteoarthritic chondrocytes (48).…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that these substances have important trophic and survival-promoting effects for the nervous system [Levi-Montalcini, 1987;Linnarsson et al, 2000]. Recent evidence indicates that they also have such effects for chondrocytes [Iannone et al, 2002]. NTs are suggested to be important in the regulation of bone formation [Asaumi et al, 2000], in the healing of skin ulcers [Aloe, 2004] and in wound healing in diabetic mice [Muangman et al, 2004].…”
mentioning
confidence: 99%